An investigation into the usefulness of the techniques for guessing the meaning of new words through context for the 11th form students at Phuc Thanh High School = Nghiên cứu lợi ích của thủ thuật đoán nghĩa từ mới dựa vào ngữ cảnh cho học sinh lớp 11 tại - Phạm, Thị Hoa (University of Languages and International Studies, 2017)
46 p. + CD-ROM